2017
DOI: 10.5194/gmd-10-3189-2017
|View full text |Cite
|
Sign up to set email alerts
|

eddy4R 0.2.0: a DevOps model for community-extensible processing and analysis of eddy-covariance data based on R, Git, Docker, and HDF5

Abstract: Abstract. Large differences in instrumentation, site setup, data format, and operating system stymie the adoption of a universal computational environment for processing and analyzing eddy-covariance (EC) data. This results in limited software applicability and extensibility in addition to often substantial inconsistencies in flux estimates. Addressing these concerns, this paper presents the systematic development of portable, reproducible, and extensible EC software achieved by adopting a development and syst… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
3

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 48 publications
0
38
0
Order By: Relevance
“…A detailed description of flux estimation using eddy covariance is provided by Aubinet et al (2012). Here fluxes were calculated using the eddy4R routines (Metzger et al, 2017). The flux (Fx) of each compound was determined by calculating the covariance function between the vertical wind velocity (w) and the VOC mixing ratio (VMRx):…”
mentioning
confidence: 99%
“…A detailed description of flux estimation using eddy covariance is provided by Aubinet et al (2012). Here fluxes were calculated using the eddy4R routines (Metzger et al, 2017). The flux (Fx) of each compound was determined by calculating the covariance function between the vertical wind velocity (w) and the VOC mixing ratio (VMRx):…”
mentioning
confidence: 99%
“…For the latent heat flux only 6 % of the data are less than 0 W m −2 or more than 110 W m −2 . We interpret these as a spurious yet systematic process that the machine learning technique cannot yet de- (Lin et al, 1983) Longwave radiation Rapid Radiative Transfer Model (Mlawer et al, 1997)…”
Section: Environmental Response Functions Of Energy Fluxesmentioning
confidence: 99%
“…For measurements over tall canopies in forested and urban environments, it has been shown that 30 min averaging intervals are quite suitable for surface layer measurements and that averaging periods up to 1 h can be feasible. Longer averaging periods often suffer from nonstationary conditions (Moncrieff et al, 2004). Averaging periods that are too short will systematically lead to an underestimation of the measured flux (e.g., Massman and Clement, 2004).…”
Section: Introductionmentioning
confidence: 99%